Monitor system development of liquid desiccant dehumidification system - Tang, Kenneth Weijie (2014)
With an increase of the threat posed by the conventional refrigerant to the environment, more attention is paid on energy conservation and efficiency maximization. Dehumidification is a method to extract moisture from air and is widely used in industries and agricultural areas. In addition, the humidity levels can be controlled by the dehumidification system to improve the health and comfort level of everyone in the building. Compared to the traditional dehumidification system, liquid desiccant dehumidification systems are proven to be an effective method because of its low energy consumption and are environmental friendly. The performance of the dehumidification system can be improved by developing a monitoring system using LabVIEW to ensure that the system is always running smoothly, optimally and safely.